Impact of a dry inoculum deposition on the efficacy of copper-based antimicrobial surfaces. Issue 3 (November 2020) - McDonald, M.; Wesgate, R.; Rubiano, M.; Holah, J.; Denyer, S.P.; Jermann, C.; Maillard, J-Y.
Summary: Background: The introduction of antimicrobial surfaces into healthcare environments is believed to impact positively on the rate of healthcare-associated infections by significantly decreasing pathogen presence on surfaces. Aim: To report on a novel efficacy test that uses a dry bacterial inoculum to measure the microbicidal efficacy of antimicrobial surfaces. Methods: An aerosolized dry inoculum of Staphylococcus aureus or Acinetobacter baumannii was deposited on copper alloy surfaces or a hospital-grade stainless-steel surface. Surviving bacteria were enumerated following incubation of the inoculated surfaces at an environmentally relevant temperature and relative humidity. Damage caused to bacteria by the aerosolization process and by the different surfaces was investigated. Findings: Dry inoculum testing showed a <2-log10 reduction in S. aureus or A. baumannii on the copper alloy surfaces tested after 24 h at 20°C and 40% relative humidity. Potential mechanisms of action included membrane damage, DNA damage and arrested cellular respiration. The aerosolization process caused some damage to bacterial cells. Once this effect was taken into account, the antimicrobial activity of copper surfaces was evident. Conclusions: Our test provided a realistic deposition of a bacterial inoculum to a surface and, as such, a realistic protocol to assess the efficacy of dry antimicrobial environmental surfaces in vitro .